Cellulase and xylanase production by A. uvarum in solid-state fementation using a packed-bed bioreactor - Salgado, José Manuel (2014)
Wastes from olive oil and wine industries (as exhausted grape mark, vineshoot trimmings, olive pomace and vinasses) were used as substrate for lignocellulolytic enzymes production (as endocellulases, endoxylanase) by solid state fermentation in a packed-bed bioreactor. In previous works, A. uvarum was selected as suitable fungus to produce cellulases and xylanases, also composition of substrate, temperature and moisture content were optimized. An important parameter in packed-bed bioreactors is air flow rate, thus its effect on enzymes production was studied. The highest enzyme production was obtained for the lower aeration rate (0.2 L/min). It was observed that increasing air flow the enzyme production was lower.